Martin Murphy (2015), The Duchess of Rio Tinto. The Story of Mary Herbert and Joseph Gage, Typeset and printed by Holywell Press, Oxford, 135 pp.doi: http://dx.doi.org/10.25267/Cuad_Ilus_romant.2018.i24.41 - Fernando Durán López (Cuadernos de Ilustración y Romanticismo)
Review